Relationship between maternal healthcare utilisation and empowerment among women in Bangladesh: evidence from a nationally representative cross-sectional study - Bishwajit Ghose; Asibul Islam Anik; Md. Mosfequr Rahman (BMJ Open, 2021)
Objective To examine the relationship between women’s empowerment and maternal healthcare utilisation in Bangladesh.Design This cross-sectional study uses data from the most recent nationally representative Bangladesh Demographic and Health Survey, 2017–2018.Setting Bangladesh.Participants Married women aged 15–49 years who had a live birth within the 3 years preceding the survey (n=4767).Primary and secondary outcome measures Women’s empowerment was measured using the recently developed and validated survey-based Women’s emPowERment (SWPER) index. The index includes three domains: social independence, decision-making and attitude to violence. Outcomes included utilisation of at least one antenatal care from skilled providers (ANC1), at least four antenatal care visits (≥4 ANC), delivery assisted by a skilled birth attendant (SBA) and a postnatal visit within 2 days of delivery (PNC). Logistic regression analyses were used to assess the identified relationships.Results Among participants, 83% received ANC1, 46.3% received ≥4 ANC, 51.9% reported SBA and 50.9% sought PNC. Women with high levels of social empowerment relative to those with low levels were more likely to use ANC1 (adjusted OR (AOR) 1.85; 95% CI 1.40 to 2.45), ≥4 ANC (AOR 1.55; 95% CI 1.27 to 1.90), SBA (AOR 2.12; 95% CI 1.71 to 2.62) and PNC (AOR 1.95; 95% CI 1.56 to 2.44). Compared with women with low levels of decision-making empowerment, women with high levels were more likely to use SBA (AOR 1.49; 95% CI 1.21 to 1.83) and PNC (AOR 1.47; 95% CI 1.19 to 1.81). Additionally, significant inequality was observed among women moving from low to high empowerment in all domains of the empowerment index.Conclusions Higher empowerment levels were positively associated with maternal healthcare utilisation in Bangladesh. Our findings suggest the need to address women’s empowerment in policies aiming to expand health service utilisation.